Handling Time Difference of Weight, Proximate Composition, and Amino Acid on Steamed Crab - Ruddy Suwandi; Nurjanah Nurjanah; Santri Maharani (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Blue swimmer crab (Portunus sp.) is one of the aquatic products which also the member of crustacea with high value as local commodity and export commodity. Weight changes in blue swimmer crabs can occur during handling time and steam process. This research aimed to determine different handling time on weight changes, proximate composition and amino acids of blue swimmer crab (Portunus sp.). The handling times used in this research were 0 hours (J0), 2 hours (J2), 4 hours (J4), 6 hours (J6) conditioned in ambient temperature. Weight lost before and after steam process of blue swimmer crabs showed significant differences in J6. Proximate compositions did not show significant differences in J0 and J6. Amino acids analysis determined by HPLC method and and did not show significant differences in J0 and J6 except for methionine, histidine, arginine, serine, and glutamic acid.